2011
DOI: 10.1136/thoraxjnl-2011-200346
|View full text |Cite
|
Sign up to set email alerts
|

Lung irradiation induces pulmonary vascular remodelling resembling pulmonary arterial hypertension

Abstract: Background Pulmonary arterial hypertension (PAH) is a commonly fatal pulmonary vascular disease that is often diagnosed late and is characterised by a progressive rise in pulmonary vascular resistance resulting from typical vascular remodelling. Recent data suggest that vascular damage plays an important role in the development of radiation-induced pulmonary toxicity. Therefore, the authors investigated whether irradiation of the lung also induces pulmonary hypertension. Methods Different sub-volumes of the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 61 publications
3
52
0
1
Order By: Relevance
“…42 In 1 case, lung irradiation in rats resulted in disruption of the endothelium in the pulmonary vasculature, followed by vascular remodeling and PAH. 43 Interestingly, this effect was not seen in mice receiving control BM cells. The pulmonary vasculature is the first capillary bed that the CD133 ϩ cells encounter after IV injection.…”
Section: Discussionmentioning
confidence: 98%
“…42 In 1 case, lung irradiation in rats resulted in disruption of the endothelium in the pulmonary vasculature, followed by vascular remodeling and PAH. 43 Interestingly, this effect was not seen in mice receiving control BM cells. The pulmonary vasculature is the first capillary bed that the CD133 ϩ cells encounter after IV injection.…”
Section: Discussionmentioning
confidence: 98%
“…Previously, we found that radiation-induced pulmonary vascular remodeling is an important factor in the development of RILT resulting in pulmonary hypertension and RV hypertrophy that eventually leads to cardiopulmonary dysfunction [14,15]. In Fig.…”
Section: Ace Inhibition Does Not Protect the Pulmonary Vasculature Afmentioning
confidence: 98%
“…RILT traditionally is divided into an early inflammatory phase, termed ''radiation pneumonitis'', and a late fibro productive phase, termed ''fibrosis''. Recently, in a preclinical model, we found that, in concert with inflammation, radiation-induced vascular remodeling played a major role in the etiology of early RILT [14]. It was shown that lung irradiation induced early pulmonary vascular remodeling which resulted in pulmonary hypertension and right ventricle (RV) hypertrophy which eventually lead to cardiopulmonary dysfunction.…”
Section: Introductionmentioning
confidence: 97%
“…The inflammatory responses appear to dictate the severity of lung remodeling, but overall, this form of lung fibrosis is associated with low mortality (106). Regarding a major feature of this model, the pulmonary vascular remodeling that occurs is reminiscent of pulmonary arterial hypertension (110). The pathobiology of irradiation-induced fibrosis is believed to involve free radical-mediated DNA damage and the induction of TGF-b.…”
Section: Radiation-induced Fibrosismentioning
confidence: 99%